Restoration of Damaged Masonry Vaulted Ceilings of Buildings - Evgeny V. Khorkov; Ilshat T. Mirsaypov (Железобетонные конструкции)
In this article, the authors present the results of a study of unreinforced and reinforced stone vaulted ceilings, which included numerical and physical experiments. We have also developed our own constructive measures to strengthen stone vaulted ceilings, based on the introduction of composite flexible rods into the body of the luggage in optimal places and, in turn, allowing to increase the efficiency and safety of work. The article presents the process of creating a homogeneous and heterogeneous model, which made it technically possible to solve problems with modeling reinforcement in masonry.